Friends’ Influence on Academic Performance Among Early Adolescents: The Role of Social Status - Palacios, Diego; Berger, Christian (Psykhe, 2022)
Educational research has shown that academic achievement and peer relationships are associated from early school years, where friends play a significant role in influencing students’ school adjustment, attitudes, and behaviors. The present study examines how individual academic performance is associated with friendships among 240 5th and 6th graders. The information on students’ friendships, academic performance, gender, popularity, and social preference was collected in a convenience sample from 8 classrooms of 2 private-subsidized schools in Santiago, Chile. Longitudinal social network analysis (RSiena) was used to study the co-evolution of academic performance and friendship dynamics, by assessing simultaneously selection and influence processes, and by incorporating social status covariates (popularity and social preference) as moderators of friendship selection and influence. Results showed that friendships were more likely to occur between same-sex peers and between students with similar social status. Regarding social influence, friends influenced individual’s academic performance. Moreover, socially preferred students were more likely to be influenced by friends’ academic performance, but the same did not occur for popular students. These results might suggest that socially preferred students’ attributes (cooperation, reciprocity, and high-quality friendships) would facilitate the influence of academic performance. In contrast, popular students would be less sensitive to their friends’ academic performance focusing instead on salient behaviors (e.g., aggression). The findings underline the importance of understanding social network dynamics in educational settings.